EXTERNAL DEMAND DETERMINANTS FOR EGYPTIAN FROZEN VEGETABLES - Sahar Abdl Elrazek; A. Abdelmaqsoud; Eman Yossif; M. Salem (Arab Universities Journal of Agricultural Sciences, 2020)
The frozen vegetable industry in Egypt is one of the most important industries that contribute to the provision of vegetables throughout the year to the consumer, and the Egyptian frozen vegetables value of exports of preserved food industries as the may reach $86.61 million on average for the period (2011-2015) with relative importance of 47.68%. The problem statement of research represent that the agricultural production in general and from vegetables and fruits in particular and the high percentage of lost and damaged, which threatens the development of Egyptian exports of these products if the export of Egyptian manufactured products does not keep pace with its international counterparts, Therefore, the research aimed to estimate the external demand for Egyptian frozen vegetables, and the determinants of that demand in the most important import markets of Egypt during the period (2007-2018). The research has reached some conclusions, including That Saudi Arabia, The United Arab Emirates, Jordan, the United States of America, Italy, and France are the most important countries importing Egyptian frozen vegetables, where the percentage of Egypt's exports of frozen vegetables to these countries amounted to about 57.1% of the total amount of Egyptian frozen vegetables exported during the period (2014-2018) Egypt's exports of frozen vegetables to these countries amounted to about 55.6% of the total value of Egyptian frozen vegetable exports for the same period. The high price elasticity of Egyptian frozen vegetables for the UAE market compared to the Saudi market with a value of about 1.5, 0.46 respectively, which means that the individual demand for frozen Egyptian vegetables for the Emirates is elastic, while the individual demand for frozen Egyptian vegetables for Saudi Arabia is inelastic. This reflects the importance of Egyptian frozen vegetables in the Saudi market and deal with them as a necessary commodity at a time when this importance is diminishing in the UAE market, where dealing with frozen Egyptian vegetables as a luxury goods. The same table also shows the increase cross elastisates of the Italian market by about 2.3 compared to the Saudi market, where the cross elasticity of those markets where 2.3, 1.3 respectively, which means that the degree of competition in the Italian market is higher than the rest of the markets. The italian market's income elasticity is also shown to be higher compared to the UAE and US market with a value of about 6.5, 2.2, 0.66 respectively. The methods of estimating the individual demand for Egyptian frozen vegetables using import statistics and using export statistics indicate different types of elastisates for the demand for Egyptian frozen vegetables for the Italian market and the Saudi and Emirati market from elastic demand to inelastic demand, which indicates the existence of Tri-Market Operation of Egyptian frozen vegetables are in these markets. The need to increase Egyptian efforts to revive the Egyptian frozen vegetable market in the UAE market as one of the most important export markets for these goods. Try to export directly to the countries which it is already exported by identifying the countries importing from Egypt to be an effective and real demand and not an indirect demand.